Carbide formation in electric-discharge-sintered Ti3Al compact caused by steric acid in ball-milled Ti and Al powder mixture. Issue 16 (November 2018) - Lee, W.H.; Cheon, Y.W.; Kim, K.B.; Yoon, Y.H.; Jeong, C.H.; Kim, Y.H.; Van Tyne, C.J.; Chang, S.Y.
Abstract: Elemental Ti and Al powders with a composition of Ti-25 at% Al, with and without 2 wt% steric acid as a process control agent, were ball-milled at 1000 rpm for 1 h using a Spex mill/mixer. The prepared powder mixture was then consolidated using an electric discharge sintering (EDS) with a 450 μF capacitor at an input voltage of 1.5–1.7 kV. The ball-milling process did not alter the original phase and composition of the elemental Ti and Al powders regardless of the addition of steric acid. However, the EDS of the ball-milled powder mixture with the steric acid formed nano-scaled Ti3 AlC2 particles, which were embedded in the grains of the Ti3 Al. The resulting compressive yield strength of the Ti3 Al-Ti3 AlC2 composite compact was about 1935 MPa, which is over twice the amount of the EDS compact obtained using the ball-milled powder mixture without the steric acid. In this paper, the fabrication method of the Ti3 Al-Ti3 AlC2 composite compact using an EDS process is reported for the first time, and the formation sequence and the strengthening mechanisms are discussed.